FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KOTA DAN KABUPATEN SEMARANG - Weni Anggraheni, 07.05.52.0011; Kartika, Andi (Students Journal of Accounting and Banking, 2013)
Land and Building Tax (PBB) is the central government taxes are mostly the results submitted to the local government. This study wanted to measure the size of the effect of independent variables consisting of GDP per capita, the amount of land area, and population of the land and building tax revenues in the City and County of Semarang. Data obtained from the Central Statistics Agency (BPS) and the Office of the Directorate General of Taxation Central Java I by the year period from 1995 to 2009, in order to obtain a sample number 30. Required fields are GDP per capita, the total area Lahas, population and land and building tax revenues. From the processing of multiple linear regression concluded that GDP per capita has positive and significant impact on revenue and Building Tax, Land Number of variables does not significantly influence the Earth Revenue And Building, variable number of residents have a positive and significant impact on land and building taxrevenues.Keywords: GDP per capita, Total Land Area, Population Actual Revenue Land and Building Tax.